LEARNER CENTERED APPROACHES IN EFL : A LITERATURE REVIEW FROM ISLAMIC EDUCATIONAL PERPSPECTIVES - Hasibuan, Kalayo; Samsul Arifin , Muhammad; Agustia, Nada; Nafiis Kelanit, M Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learner-Centered Approaches in EFL: A Literature Review from Islamic Educational Perspectives. This study is a literature review that examines learner-centered approaches in English as a Foreign Language (EFL) instruction from Islamic educational perspectives. The study is motivated by the shift from traditional teacher-centered instruction to learner-centered pedagogy, which emphasizes students’ autonomy, active participation, collaboration, and responsibility in the learning process. In addition, the integration of Islamic values is considered important to support learners’ holistic development, including cognitive, affective, and moral dimensions. This research employs a narrative literature review method by analyzing relevant scholarly articles, books, and previous studies related to EFL instruction, learner-centered pedagogy, and Islamic education. The findings reveal that learner-centered approaches such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and Project-Based Learning (PBL) enhance students’ motivation, engagement, and communicative competence. Furthermore, Islamic educational values such as tarbiyah, ta’lim, and ta’dib, as well as amanah, ta’awun, and adab, are aligned with learner-centered principles and can be integrated into classroom practices. However, several challenges remain, including limited teacher readiness, traditional classroom culture, and lack of empirical studies in Islamic educational contexts, particularly in Indonesia. Therefore, this study highlights the need for further research on practical implementation of learner-centered EFL instruction integrated with Islamic values in diverse educational settings